Evidence for a Role of Orexin/Hypocretin System in Vestibular Lesion-Induced Locomotor Abnormalities in Rats - Pan, Leilei; Qi, Ruirui; Wang, Junqin; Zhou, Wei; Liu, Jiluo; Cai, Yiling (Frontiers in Neuroscience, 2016)
Vestibular damage can induce locomotor abnormalities in both animals and humans. Rodents with bilateral vestibular loss showed vestibular deficits syndrome such as circling, opisthotonus as well as locomotor and exploratory hyperactivity. Previous studies have investigated the changes in the dopamine system after vestibular loss, but the results are inconsistent and inconclusive. Numerous evidences indicate that the orexin system is implicated in central motor control. We hypothesized that orexin may be potentially involved in vestibular loss-induced motor disorders. In this study, we examined the effects of arsanilate- or 3, 3′-iminodipropionitrile (IDPN)-induced vestibular lesion (AVL or IVL) on the orexin-A (OXA) labeling in rat hypothalamus using immunohistochemistry. The vestibular lesion-induced locomotor abnormalities were recorded and verified using a histamine H4 receptor antagonist JNJ7777120 (20 mg/kg, i.p.). The effects of the orexin receptor type 1 antagonist SB334867 (16 μg, i.c.v.) on these behavior responses were also investigated. At 72 h post-AVL and IVL, animals exhibited vestibular deficit syndrome and locomotor hyperactivity in the home cages. These responses were significantly alleviated by JNJ7777120 which also eliminated AVL-induced increases in exploratory behavior in an open field. The numbers of OXA-labeled neurons in the hypothalamus were significantly increased in the AVL animals at 72 h post-AVL and in the IVL animals at 24, 48 and 72 h post-IVL. SB334867 significantly attenuated the vestibular deficit syndrome and locomotor hyperactivity at 72 h post-AVL and IVL. It also decreased exploratory behavior in the AVL animals. These results suggested that the alteration of OXA expression might contribute to locomotor abnormalities after acute vestibular lesion. The orexin receptors might be the potential therapeutic targets for vestibular disorders.